2020
DOI: 10.3390/nu12071985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Taste on Food Choices in Adolescence—Systematic Review and Meta-Analysis

Abstract: Studies of adults report that perceived taste affects food choices and intake, which in turn may have an impact on health. However, corresponding evidence on adolescents is limited.  Our aim was to summarize current evidence of the impact of taste perception on food choice preferences or dietary intakes among adolescents (mean age 10–19.9 years). Systematic searches identified 13 papers, 12 cross-sectional and one cohort study published between 1 January 2000 to 20 February 2020 assessing the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
(170 reference statements)
2
19
1
2
Order By: Relevance
“…Previous literature often cites the taste or physical properties of food as a top factor in food choices, among both adults (Köster, 2009) and adolescents (Neumark-Sztainer et al, 1999;Contento et al, 2006;Holsten et al, 2012;Sommer et al, 2014;Bawajeeh et al, 2020). However, we found that taste was only a predominant factor in discussions about food choices at school.…”
Section: Factors In Adolescent Food Choicescontrasting
confidence: 58%
“…Previous literature often cites the taste or physical properties of food as a top factor in food choices, among both adults (Köster, 2009) and adolescents (Neumark-Sztainer et al, 1999;Contento et al, 2006;Holsten et al, 2012;Sommer et al, 2014;Bawajeeh et al, 2020). However, we found that taste was only a predominant factor in discussions about food choices at school.…”
Section: Factors In Adolescent Food Choicescontrasting
confidence: 58%
“…Adolescents belonging to this cluster declared high preference only for snacks and fruit but not for other products. Such observation is in compliance with other studies, which confirm that younger-aged individuals show a higher preference toward products characterized by a high content of sugar [ 38 ]. It corresponds with the fact that in our own study, the ‘hedonists’ cluster more often declared buying pastries or cakes than two other clusters, both in the female and male subgroups.…”
Section: Discussionsupporting
confidence: 93%
“…Both school and clinical study samples had fun parks as the highest rated item, followed by less healthy foods/beverages and activities, and the healthiest items rated as least liked. Greater preferences were observed for sweet, salty, and fatty foods—as well as lower liking of healthier foods with strong flavors and textures—which is consistent with preference patterns in adolescents that are influenced by genetic and sensory nutrition influences [ 40 ]. Strong taste, flavor, and/or texture are key determinants of vegetable preference in children [ 41 ] and adults [ 42 ] and, in multivariate modeling, social-behavior factors influencing the preference for vegetable, which in turn, influencing the consumption of vegetables [ 43 ].…”
Section: Discussionmentioning
confidence: 55%